Ecological Culture in the Traditional Worldview of the Turks (Tengriism and folk Islam) - Amirovna, Kasymbekova Marzhan; Zhenisuly, Zhengis Zhomart; Zhanymkhan, Oshan; Kabdeshuly, Zhumadil Arman; Yeldos, Sauyrkan (Journal of Ecohumanism, 2025)
Today, one of the most significant global threats to international security is environmental issues. In the modern world, key environmental challenges include ozone layer depletion, global warming, air pollution, the greenhouse effect, ocean pollution, and the loss of biodiversity on Earth. Religion, as a core element of any culture and civilization, shapes the worldview of an ethnic group and its relationship with the natural environment. Religions can be divided into “ecological” and “non-ecological” categories. This article examines the issue from the perspective of the traditional worldview of the Turkic peoples, which is regarded as an ecological religion